Eigencurves for a Steklov problem - Aomar Anane; Omar Chakrone; Belhadj Karim; Abdellah Zerouali (Electronic Journal of Differential Equations, 2009)
In this article, we study the existence of the eigencurves for a Steklov problem and we obtain their variational formulation. Also we prove the simplicity and the isolation results of each point of the principal eigencurve. Also we obtain the continuity and the differentiability of the principal eigencurve.